Lattice dynamics in elemental modulated Sb2Te3 films. Issue 3 (3rd September 2015) - Bessas, D.; Winkler, M.; Sergueev, I.; König, J. D.; Böttner, H.; Hermann, R. P.
Abstract: The crystallinity and the lattice dynamics in elemental modulated Sb 2 Te 3 films are investigated microscopically using high energy synchrotron radiation diffraction combined with 121 Sb nuclear inelastic scattering. The correlation length is found to be finite but less than 100 Å. The element specific density of phonon states is extracted. A comparison with the element specific density of phonon states in bulk Sb 2 Te 3 confirms that the main features in the density of phonon states arise from the layered structure. The average speed of sound at 40 K, 1.74 ( 2 ) km s − 1, is almost the same compared to bulk Sb 2 Te 3 at 20 K, 1.78 ( 2 ) km s − 1 . Similarly, the change in the acoustic cut‐off energy is within the experimental detection limit. Thus, we suggest that the lattice thermal conductivity in elemental modulated Sb 2 Te 3 films should not be significantly changed from its bulk value.